STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBINA DAN MEMBENTUK AKHLAKUL KARIMAH SISWA ( STUDI ETNOGRAFI DI SEKOLAH MENENGAH PERTAMA NEGERI 2 DONOMULYO ) - Irfan Musadat, Maulidia Nafi’atul Khorimah (JIPI (Jurnal Ilmiah Pendidikan Islam), 2023)
This study focuses on the strategies of PAI teachers in fostering and forming students' morals at SMP Negeri 2 Donomulyo. This study uses a type of qualitative research with an ethnographic approach. Data collection techniques are by observation, interviews and documentation. The data analysis technique uses data reduction, data presentation and verification. The purpose of this research is to find out the strategies of PAI teachers in fostering and forming akhlakul karimah students of SMP N 02 Donomulyo. While the conclusions and results of this study indicate that the moral condition of students at SMP Negeri 2 Donomulyo in attitude, behavior, and language in general is quite good. The strategy used by PAI teachers in forming and fostering student morals at SMP Negeri 2 Donomulyo is by exemplary and habituation methods, as well as compiling activity programs that can assist in fostering student morality